How to succeed at globalization : a primer for roadside vendors - El Fisgón (New York : Metropolitan Books : Henry Holt and Co., 2004)
The Mexican cartoonist serves up a stinging satirical attack on capitalism, offering an hilarious but hard-hitting history of globalization that takes readers from the Middle Ages to a modern faith healer working in the Arizona desert, all the while exposing the greed and callousness of the free market system.
Prijevod djela: Hacia un despiporre global de excelencia y calidad
Keywords: međunarodni ekonomski odnosi -- karikature i stripovi -- globalizacija -- ekonomsko gledište